Magnesium: a scoping review for Nordic Nutrition Recommendations 2023 - Christine Henriksen; Jan Olav Aaseth (Food & Nutrition Research, 2023)
Magnesium is a divalent ion involved in a range of biochemical reactions and cellular functions. The metabolism and requirements for magnesium are still insufficiently understood. In the Nordic Nutrition Recommendations from 2012, a recommended intake was set based on balance studies. However, the average requirement (AR) was not set. Functional indicators of magnesium status have been lacking. This scoping review reveals new research activity related to the beneficial effect of magnesium intake on several health outcomes (cardiovascular disease, diabetes and some cancers). Based on meta-analyses of cohort studies and Randomized Controlled Trials (RCTs), as well as on plausible mechanisms, a causal association is suggested. However, the optimal intake cannot be set based on these study designs and no new balance studies were found.